Administrative procedures’ conduct in the field of investment under the provisions of Law No. 22-18 - MEZHOUD, Elhachemi (Journal of Human Sciences, 2025)
Administrative procedures for completing various stages and processes of investment are topics of great importance from a theoretical and practical point of view, as simple and quick procedures and the presence of bodies tasked with accompanying investors from an administrative point of view contribute to the most important requirements for improving the investment environment in a country. The Algerian Legislature has approved through Law No. 22-18, related to investment, a set of new facilities and incentives with regard to the administrative track of accompanying and embodying investments, whether related to expanding the role of the National Investment Council, the powers of the Algerian agency for investment promotion and the creation of a digital platform at its disposal, or the establishment of the Supreme In addition to easing the procedures related to granting economic real-estate directed to the embodiment of investment projects. Finally, we have concluded that legal amendments related to the course of administrative procedures will not be sufficient alone, unless they are accompanied by institutional performance that embodies them and goes beyond the traditional management that governs it.